Analisis Saluran Dan Margin Pemasaran Telur Ayam Kampung (Gallus Domesticus) di Kotamadya Pematang Siantar - Ginting, Rendel Herbert; Daulay, Armyn Hakim; Hutauruk, Julia (JURNAL AGRIUST, 2022)
The purpose of this research is to analyze the marketing system and channel of chicken eggs and analyze marketing efficiency from marketing margin, price share and profit ratio of chicken egg cost in Pematangsiantar Municipality of Simalungun Regency.. The method used in data collection is 1. Sampling of breeders and other marketing institutions selected by snowboling sampling technique and data collection methods is done by interviewing techniques using quisioner. Data analysis includes marketing costs, marketing margin, farmer / breeder share and profit cost ratio of each marketing channel. The results of this study indicate that there are four marketing channels. The marketing margin on the second channel shows the smallest cost margin and the largest profit margin so that it shows the largest cost-benefit ratio. The largest farmer share is obtained on the fourth channel but this channel uses only the retailer as an intermediate channel (1 level) and relatively few exchanged eggs. So it is concluded that the second channel is the most efficient channel because the smallest cost and benefits are spread evenly in all the marketer institutions that play a role. The need for chicken eggs in the municipality siantar siantar (63.33%) supplied from outside the city and (36.66%) filled by breeders from within the city.